Pendampingan Guru Bahasa Arab Pondok Pesantren Nahdlotul Ulum Kota Metro dalam Pengembangan Media Pembelajaran Bahasa Arab Berbasis Teknologi, Informasi & Komunikasi (ICT) - Muhammad Syaifullah; Nailul Izzah; Nahdla, Naila Cahya (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2023)
Islamic boarding schools are religious institutions that provide education and teaching as well as develop and disseminate Islamic religious knowledge. Learning includes human elements, materials, facilities, equipment and procedures that influence each other to achieve learning objectives, in this case humans involved in the teaching system consist of students, teachers and other personnel, the material includes; books, blackboards and others. Facilities and equipment consist of classrooms and audiovisual (learning media). Procedures include schedules and methods of delivering information, teaching practice, exams and so on. However, the lack of teacher understanding of the procedures and principles of choosing the right media results in the learning media used cannot support the learning process optimally. The steps of assistance in the process of approaching the Asset Based Communities Development (ABCD) method and tools in finding and recognizing assets are Appreciative Discovery, Asset development analysis, Program strategy analysis, Program narrative summary, Program monitoring and evaluation techniques. So it is hoped that Arabic teachers of Nahdlotul Ulum Islamic Boarding School, North Metro, Metro City can develop Arabic Learning Media Based on Technology, Information & Communication (ICT).